Discovery of a New Natural Product and a Deactivation of a Quorum Sensing System by Culturing a “Producer” Bacterium With a Heat-Killed “Inducer” Culture - Liang, Libang; Sproule, Amanda; Haltli, Brad; Marchbank, Douglas H.; Berrué, Fabrice; Overy, David P.; McQuillan, Kate; Lanteigne, Martin; Duncan, Noelle; Correa, Hebelin; Kerr, Russell G. (Frontiers in Microbiology, 2019)
Herein we describe a modified bacterial culture methodology as a tool to discover new natural products via supplementing actinomycete fermentation media with autoclaved cultures of “inducer” microbes. Using seven actinomycetes and four inducer microbes, we detected 28 metabolites that were induced in UHPLC-HRESIMS-based analysis of bacterial fermentations. Metabolomic analysis indicated that each inducer elicited a unique response from the actinomycetes and that some chemical responses were specific to each inducer-producer combination. Among these 28 metabolites, hydrazidomycin D, a new hydrazide-containing natural product was isolated from the pair Streptomyces sp. RKBH-B178 and Mycobacterium smegmatis. This result validated the effectiveness of the strategy in discovering new natural products. From the same set of induced metabolites, an in-depth investigation of a fermentation of Streptomyces sp. RKBH-B178 and autoclaved Pseudomonas aeruginosa led to the discovery of a glucuronidated analogue of the pseudomonas quinolone signal (PQS). We demonstrated that RKBH-B178 is able to biotransform the P. aeruginosa quorum sensing molecules, 2-heptyl-4-quinolone (HHQ) and Pseudomonas quinolone signal (PQS), to form PQS-GlcA. Further, PQS-GlcA was shown to have poor binding affinity to PqsR, the innate receptor of HHQ and PQS.